How to change a constitution by hand-waving (Or, the unbearable lightness of evidence in support of lifting foreign ownership restrictions) - Toby C. Monsod; Aleli D. Kraft; Cielo Magno; J. C. Punongbayan; Orville Jose C. Solon; Elizabeth Tan; Agustin L. Arcenas; Florian A. Alburo; Emmanuel S. de Dios (University of the Philippines, School of Economics (UPSE), 2024)
This paper provides a review of the empirical evidence cited in the current public discussions on removing the remaining constitutional restrictions on foreign-equity ownership in certain economic sectors. A fuller appreciation of the given evidence shows that lifting equity restrictions is not a necessary condition for explaining the inward stocks of foreign direct investment (FDI) in the cited countries, including the Philippines. While restrictive equity rules may represent a hindrance to FDI, their potential effects are small and sometimes insignifcant in comparison to other explanatory variables such as the ease of doing business, physical infrastructure, and perceived corruption. The paper cautions against an uncritical mindset towards FDI, discussing how consistent empirical evidence of the positive effects of FDI on host economies has proved elusive and that knowledge and technological spillovers from FDI are highly contextspecifc, not unconditional, and not without cost. Instead, a more discriminating approach, focusing on the quality of multinational enterprises and its activities, rather than simply on the volume of FDI, is recommended. Finally, the paper warns that the push for legislative fexibility, while attractive on the surface, can be self-defeating since it also has the potential of increasing investment uncertainty, particularly given the idiosyncrasies of Philippine political economy.
Keywords: 330; foreign direct investment; multinational enterprises; foreign equity restrictions; constitutional change; empirical models of investment distribution; infuences on the distribution of direct foreign investments; rules versus discretion